Status Concerns as a Motive for Crime? - Florian Baumann; Tim Friehe (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper analyzes the implications of potential offenders caring about their relative status. We establish that subjects' status concerns can result in multiple-equilibrium crime rates and may modify the standard comparative-statics results regarding how the crime rate changes in response to a higher detection probability and higher sanctions. In addition, we argue that the socially optimal level of the detection probability and the sanction will often be higher when potential offenders care about their relative positions. Our analysis can be linked to one of the most important criminological theories of crime, namely strain theory.
Keywords: H23; K42; 330; crime; status; deterrence; multiple equilibria; strain theory